Pengembangan Soal Matematika Serupa Pisa Dalam Konten Space And Shape Pada Siswa Kelas VIII - Maharani, Pipit; , Prof. Dr. Budi Murtiyasa, M.Kom (2015)
This research aims to design similar PISA math problem in space and shape content. The method used in this research is the research and development that is research development. This study requires two essential stages, namely self evaluation and prototype, which includes the preparation phase of self evaluation and design, while the prototype stage includes expert reviews, one-to-one, small group, and a field test. Data collection techniques used by the walkthrough and analysis of documents. After going through the one-to-one, small group and validation qualitative descriptive matter in tested right at the stage of field test in class VIII SMP N 2 F Jaten. The test results overall with an average value of mathematical reasoning abilities 54.531, including the category of mathematical reasoning ability is enough, although there are still some students who enter the category of less. However, these results can also be said that similar PISA math problem can give potential effects on students' mathematical reasoning abilities.